Microarray analysis of global gene expression in leukocytes following lithium treatment. (7th January 2014) - Watanabe, Shinya; Iga, Junichi; Nishi, Akira; Numata, Shusuke; Kinoshita, Makoto; Kikuchi, Kumiko; Nakataki, Masahito; Ohmori, Tetsuro
<x xml:space="preserve">Abstract</x> Objectives To elucidate the molecular effects of lithium, we studied global gene expression changes induced by lithium in leukocytes from healthy subjects. Methods Eight healthy male subjects participated in this study. Lithium was prescribed for weeks to reach a therapeutic serum concentration. Leukocyte counts and serum lithium concentrations were determined at baseline (before medication), after 1 and 2 weeks of medication and at 2 weeks after stopping medication. Gene expression profiling was performed at each time point using Agilent G4112F Whole Human Genome arrays (The Agilent Technologies, Santa Clara, CA, USA). Expression of some candidate genes was also assessed by real‐time polymerase chain reaction (PCR). Results Gene ontology analysis revealed that the cellular and immune responses to stimulus and stress indeed played a major role in the cellular response to lithium treatment. Pathway analysis revealed that the interleukin 6 pathway, the inhibitor of differentiation pathway, and the methane metabolism pathway were regulated by lithium. Using real‐time PCR, we also confirmed that five candidate genes in these pathways were significantly changed, including suppressor of cytokine signaling 3 and myeloperoxidase. Conclusions Our investigation suggests that the molecular action of lithium is mediated in part by its effects on the cellular and immune response to stimulus and stress followed by the interleukin 6, inhibitor of differentiation, and methane metabolism pathways. Copyright © 2014 John Wiley & Sons, Ltd.